1982
DOI: 10.1111/j.1440-1819.1982.tb00262.x
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiological Study of Autism in Fukushima-ken

Abstract: A survey of children aged under 18 years in Fukushima‐ken (prefecture) in Japan showed that 2.33 per 10,000 children suffered from early infantile autism. The average of prevalence rates of autistic children born between 1968 and 1974 was 4.96 per 10,000 children. Based on a comparison between cities and rural districts, the prevalence rates of the former were significantly higher than those of the latter. Autistic boys outnumbered autistic girls with a sex ratio of 9: 1. Psychiatric illnesses; were very rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 4 publications
5
27
0
2
Order By: Relevance
“…Early studies have agreed with Kanner's description (Hoshino, Kumashiro, Yashima, Tachibana, & Watanabe, 1982), while others have found no such association (Cialdella & Mamelle, 1989;Croen et al, 2002;Cryan, Byrne, O'Donovan, & O'Callaghan, 1996;Hoshino et al, 1982), suggesting that higher social class is not related to the risk of autism. Recent studies on the association between socioeconomic status and the risk of autism reported conflicted results (Durkin et al, 2010;King & Bearman, 2011;Rai et al, 2012).…”
Section: Socioeconomic Status and Parental Concernsupporting
confidence: 60%
“…Early studies have agreed with Kanner's description (Hoshino, Kumashiro, Yashima, Tachibana, & Watanabe, 1982), while others have found no such association (Cialdella & Mamelle, 1989;Croen et al, 2002;Cryan, Byrne, O'Donovan, & O'Callaghan, 1996;Hoshino et al, 1982), suggesting that higher social class is not related to the risk of autism. Recent studies on the association between socioeconomic status and the risk of autism reported conflicted results (Durkin et al, 2010;King & Bearman, 2011;Rai et al, 2012).…”
Section: Socioeconomic Status and Parental Concernsupporting
confidence: 60%
“…When dates of publication are used in a meta-analysis, an analysis of time trends will reveal little beyond an apparent effect of changes in diagnostic standards. An assessment (not shown) of all published prevalence studies by diagnostic criteria set (Kanner,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) Rutter/DSM-III, [46][47][48][49][50][51][52][53][54][55][56][57][58] DSM-III-R, 60,82,85-92 and DSM-IV through 2001 2, 12,20,34,61-63,66-68,73,75,78-80,92-96 ) reveals that prevalence was relatively stable until the most recent set of diagnostic criteria was introduced.…”
Section: Critical Examination Of Methods For Cross-survey Comparisonsmentioning
confidence: 99%
“…The mean prevalence rate for 11 studies using the Kanner criteria was two per 10,000. [35][36][37][38][39][40][41][42][43][44][45] This compares to a mean of seven per 10,000 for 13 surveys of infantile autism that applied either the Rutter or DSM-III criteria or similar "post-Kanner" clinical criteria. [46][47][48][49][50][51][52][53][54][55][56][57][58] Age of onset is the one criterion that has changed most measurably over time.…”
Section: Definitionsmentioning
confidence: 99%
“…The authors of the Fukushima-ken study 51 reported higher rates of autism in children born between 1966 and 1974 than in births 1960 through 1965 or after 1975. The authors considered that the reason for the lower rates of autism in children born before 1966 "was probably that autistic children had become older, lost the unique feature[s] of young autistic children and had been overlooked."…”
Section: In Human Populations Exposed To Mercury Did Autism Increase?mentioning
confidence: 99%
“…50 Definitions and methods of ascertainment were widely different in different studies, so comparisons are difficult. A study in Fukushima-ken 51 is described here in some detail because it provides an example of the issues faced by studies of prevalence during this period and includes an analysis by year of birth in an area not far distant from Niigata. In this study, conducted in 1977, the authors attempted to evaluate all children with autism 18 years old or less who were born in the province in 1960 through 1977.…”
Section: In Human Populations Exposed To Mercury Did Autism Increase?mentioning
confidence: 99%